Eksplorasi Dukungan Suami dalam Pencapaian Becoming a Mother pada Ibu Remaja - Susi Sastika Sumi; Yusnaeni Yusnaeni (Journal of Telenursing (JOTING), 2022)
This study aims to explore the experiences of teenage mothers getting husbands' support in the process of becoming a mother. The method used is a qualitative method with a phenomenological design. The results showed that there were five themes, namely: 1) the husband's support based on the initiative and request of adolescent mothers at the stage of pregnancy; 2) husbands provide support based explicitly on the needs of adolescent mothers; 3) the husband has not received the pregnancy intends to terminate and does not provide support; 4) forms of husband support: providing physical and psychological support, providing for the wife's needs, carrying out local rituals related to childbirth; 5) form of husband's support: helping to take care of the baby, willing to do household chores, reminding the duties and responsibilities as a mother, fulfilling the life needs of mother and baby. In conclusion, the husband's support is very influential in the process of becoming a mother. Keywords: Becoming a Mother, Husband Support, Teen Mother